Thermal-hydraulic evaluation of 3D printed microstructures. (September 2019) - Trevizoli, P.V.; Teyber, R.; da Silveira, P.S.; Scharf, F.; Schillo, S.M.; Niknia, I.; Govindappa, P.; Christiaanse, T.V.; Rowe, A.
Highlights: Novel 3D printed microstructures are designed as thermal regenerative matrices. Four matrices are tested: two in-line and two staggered arrangement of fibers. High thermal effectivenesses (>90%) are experimentally characterized. The matrices with an in-line arrangement presented lower viscous losses. Such geometries are promising to be applied as active magnetic regenerators. Abstract: High performance thermal regenerators require matrices with low pressure drop and high thermal effectiveness. To address this topic a new regenerator geometry is designed, manufactured and experimentally tested in a passive regenerator apparatus. Two microstructure configurations based on crossed fibers are examined, one using aligned fibers and another with staggered fibers. A total of four regenerators are tested where the fiber diameter and spacing are varied. All the matrices are made of stainless steel and distilled water is used as heat transfer fluid. The experiments are performed using operating frequencies and utilization factors typical of those in active magnetic regenerators. The regenerators are characterized and compared based on the thermal effectiveness and pressure drop. Effectiveness imbalance and temperature profiles along the regenerator bed are also presented and discussed. The results reveal that 3D printed matrices are promising geometries for active magnetic regenerators.